Hypoxia and hypoxia-inducible factors in chronic kidney disease. Issue 1 (December 2016) - Tanaka, Shinji; Tanaka, Tetsuhiro; Nangaku, Masaomi
Abstract It is generally accepted that renal hypoxia plays an important role in the progression of chronic kidney disease (CKD). This review focuses on renal hypoxia and hypoxia-inducible factor (HIF), a master regulator of cellular adaptation to hypoxia, during CKD progression. The kidney, which is physiologically hypoxic, is exposed to increased levels of hypoxia in CKD; insufficient oxygenation in the tubulointerstitium triggers injury and accelerates the deterioration of renal function, culminating in end-stage kidney disease (ESKD). HIF accumulates during specific stages of pathological progression; however, adaptation to hypoxia usually fails. In such cases, decreased vascular endothelial growth factor expression and upregulated antiangiogenic factors result in sustained capillary rarefaction. In addition, oxygen consumption in tubules is primarily increased by enhanced oxidative stress, and the transcriptional activity of HIF becomes suboptimal, which is partly mediated by methylglyoxal in diabetic kidney disease and by indoxyl sulfate, a representative uremic toxin, in advanced CKD. Oxygen-dependent canonical regulators of HIF involve prolyl hydroxylase domain-containing protein (PHD) and factor inhibiting HIF-1 (FIH-1), whereas recent studies have revealed noncanonical and oxygen-independent HIF regulation in the kidney. As a consequence, HIF accumulation usually fails to protect the kidney against hypoxia, which is likely to accelerate progression to ESKD, via several maladaptation mechanisms. The precise roles of HIF and its regulation in CKD warrant further investigation in light of promising data demonstrating that HIF stabilization by PHD inhibitors may be a new therapeutic approach for CKD.